Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan CV Tri Setya Abadi - Octavia, Ayu Nurafni; Prihatini, Puja; Saraswati, Diah Cahyani (STIE PENA, 2023)
The purpose of this study was to determine whether work motivation, work discipline, and job satisfaction affect employee performance at CV Tri Setya Abadi. The population in this study were 37 employees at CV Tri. Setya Abadi and included in this research sample. The research method to be carried out is quantitative research and this research is categorized as explanatory research, namely research that aims to explain the causal relationship between variables through hypothesis testing. The type of data used is primary data. Methods of data collection using questionnaires and documentation. The analysis technique used is the validity and reliability test, the classical assumption test (normality test, multicollinearity test and heteroscedasticity test), t test, F test and the coefficient of determination (R2). Testing the hypothesis of this study with the help of SPSS version 25. The results of this study indicate that partially there is a positive and significant influence between motivational variables and performance variables on CV. Tri Setya Abadi, there is a positive and significant influence between discipline variables and performance variables on CV. Tri Setya Abadi, there is a positive and significant influence between job satisfaction variables and performance variables on CV. Tri Setya Abadi and work motivation, work discipline and job satisfaction simultaneously have a positive and significant effect on employee performance at CV. Tri Setya Abadi.